Effects of Political Insecurity on Critical Infrastructures in Nigeria: Focus on President Goodluck Jonathan's Administration - Ugbedeojo Ameh, Emmanuel; O. Ibebunjo, Basil (Kashere Journal of Politics and International Relations, 2023)
Building resilience around facilities, setting up security measures, and starting countermeasures are some ways to protect infrastructures. Some common forms of critical infrastructures include emergency services, the energy sector, dams, food, public services, industry, health, transportation, gas, public communications, radio and television. Nigeria's nature of political insecurity has however, hampered the thriving of these infrastructures. The paper therefore sets to uncover the effects that political insecurity has had on this critical infrastructure. It uses a combination of conceptual review, theme analysis, and theoretical presentation make up the methodology. For its theoretical framework, the paper adopts Structural Functionalism. Structural functionalism is a prominent sociological theory that expounds on why society functions the way it does based on the interface between the various social institutions that make up society. The paper explores literatures of other researchers, sieving their ideas and creating a balance for a structured argument. It concludes by buttressing the fact that political insecurity is a major player in the inefficiency of the infrastructures in Nigeria. The paper therefore recommends that critical infrastructures such as education, health, transport, and power, should be given a big concentration by all levels of government. With this in place, there would be provision of employment as well as employable graduates to manage such infrastructures.